RELIGIOUS INCLUSIVESM; ISLAM, CHRISTIAN AND HINDU RELATIONS IN BESOWO KEDIRI EAST JAVA - M. Thoriqul Huda (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2023)
Indonesia has a diversity of ethnicities and religions. The Besowo community is one of the community groups in which it consists of various religions, namely Islam, Christianity and Hinduism. In this diverse life, religious people need to prioritize an inclusive attitude in religion. This study wants to see the extent to which inclusiveness in religion is understood theoretically and practically so that it can be the basis for building harmonious inter-religious relations. By using a qualitative approach, this research will look comprehensively at the relationship between Islam, Christianity and Hinduism in Besowo Kediri. The results showed that religious people in Besowo have an inclusive perspective in religion, this attitude is also manifested in religious and social life, so that a harmonious and tolerant life can be realized. This harmonious life is also strengthened by the Besowo culture which has been rooted for generations.